EKSPERIMEN PEWARNAAN BATIK DENGAN BAHAN ALAMI DAUN PACAR KUKU DI SMP IT BINA INSAN - Khoirurrahma Khoirurrahma; Sri Wiratma; Adek Cerah Kurnia Aziz (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
This research aims to find out how the process and stages are carried out to make batik colors using natural ingredient pacar kuku leaves, to find out how the results of batik coloring in terms of color evenness, color sharpness, and color absorption using natural ingredient pacar kuku leaves, and to find out how the influence of the time difference for one day, two days and theree days done when soaking batik cloth using natural ingredient pacar kuku leaves (Lawsonia Inermis L). This research is a qualitative research. The research method used is descriptive qualitative method. The population contained in this research were all first year students of Al-Ghazali Class SMP IT Bina Insan, using Purposive Sampling technique, which is a sampling technique with certain considerations. Work evaluation indicators, such as; color evenness, color sharpness, and color absorption as well as the time differences. The results showed that overall the work of batik coloring experiment with natural ingredient pacar kuku leaves (Lawsonia Inermis L) from the time differences for one day, two days and theree days obtained good category result. color evenness overall obtained good category result, color absorption obtained good category result and color sharpness obtained good category result.Keywords : Experiment, Coloring, Leaves